An open-system approach of medical professionalism: a controversy within the sociology of professions - Correia, T. (2015)
This article focuses on a specific debate within theories of professions. Despite different trends, there has been difficulty in theorizing some dimensions of the dominant perspectives because of predominant institutional attention. The aim here was to reinforce the debate with complementary conceptualization of professionalism and, consequently, to foster new understandings of professional relationships. The argument lies in shifting the analytical level from the professions to professionals, as a basic step in conceptualizing individual action within professional contexts. This concern becomes increasingly important as the professional discretion structurally held by individuals becomes greater, since the ability to choose leads more explicitly to internal differentiation of professions. Systemic influence is felt given that social structures are intrinsically involved in actions, which represent exteriorizations of individually internalized processes. Consequently, it becomes necessary to consider the reasons for behaviors and the meanings individually conferred on professional dimensions.